2016
DOI: 10.1055/s-0035-1571256
|View full text |Cite
|
Sign up to set email alerts
|

Review of Therapeutic Interventions for the Upper Limb Classified by Manual Ability in Children with Cerebral Palsy

Abstract: Cerebral palsy (CP) describes "a group of permanent disorders of the development of movement and posture, causing activity limitation, that are attributed to non-progressive disturbances that occurred in the developing fetal and infant brain. The motor disorders of cerebral palsy are often accompanied by disturbances of sensation, perception, cognition, communication and behavior, by epilepsy, and by secondary musculoskeletal problems." 1 Cerebral palsy has been historically categorized topographically and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 89 publications
1
7
0
1
Order By: Relevance
“…Furthermore, for the NR group, although it was difficult to define participant’s characteristics, the difference between the high and low groups according to the child’s functional level was < 0.1, and there was no significant difference; this may be because VR intervention can select and change the difficulty level according to participant characteristics ( Kuttuva et al, 2006 ; Popescu et al, 2000 ). According to previous studies conducted on CP children, studies confirming the effect of virtual reality according to GMFCS and MACS reported that it was effective at all functional levels or there was no difference according to level, and these results are consistent with this review ( Shierk, Lake & Haas, 2016 ; Cherni et al, 2020 ). For the reason that these results were derived, most of the subjects included in this review were in stages 1-3, and it is thought that a ceiling effect occurred ( Johnson et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, for the NR group, although it was difficult to define participant’s characteristics, the difference between the high and low groups according to the child’s functional level was < 0.1, and there was no significant difference; this may be because VR intervention can select and change the difficulty level according to participant characteristics ( Kuttuva et al, 2006 ; Popescu et al, 2000 ). According to previous studies conducted on CP children, studies confirming the effect of virtual reality according to GMFCS and MACS reported that it was effective at all functional levels or there was no difference according to level, and these results are consistent with this review ( Shierk, Lake & Haas, 2016 ; Cherni et al, 2020 ). For the reason that these results were derived, most of the subjects included in this review were in stages 1-3, and it is thought that a ceiling effect occurred ( Johnson et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…The first 30 mins of specific sensory-motor training focus on tactile discrimination function, for improving somatosensory processing. 42,43 In the remaining 30 mins, the participants received task-oriented training to improve unilateral and bilateral upper limb function. When combined with other intervention strategies, including constraint-induced movement therapy and bimanual training, SM-TOT was effective in improving hand function and self-care skills.…”
Section: Discussionmentioning
confidence: 99%
“…The SM-TOT consisted of two sections. The first 30 mins of specific sensory-motor training focus on tactile discrimination function, for improving somatosensory processing 42,43 . In the remaining 30 mins, the participants received task-oriented training to improve unilateral and bilateral upper limb function.…”
Section: Discussionmentioning
confidence: 99%
“…This information informs the selection of appropriate therapeutic interventions and strategies to improve hand function and manual dexterity. By tailoring treatment plans to an individual's specific MACS level, therapists can design realistic, effective, and targeted interventions to address their unique needs [ 37 ].…”
Section: Reviewmentioning
confidence: 99%